Evaluation of The National Mental Revolution Movement Policy in Increasing Inter and Intra-Religious Tolerance and Harmony (Study in The Special Capital Region of Jakarta Province) - Fahrurozi, Mukhammad; Simangunsong, Fernandes (Journal Of Social Science (JoSS), 2025)
This study aims to evaluate the policies of the National Movement for Mental Revolution (GNRM) in increasing tolerance and inter-religious harmony in DKI Jakarta Province. The problems behind this study are the increase in hoaxes, hate speech, intolerance and radicalism in society, as well as the erosion of the values of mutual cooperation and unity. The underlying theory of this study is the Stufflebeam evaluation model with the CIPP (Context, Input, Process, Product) approach. This study uses a qualitative method with an analytical descriptive approach. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies. The research informants consisted of 20 people representing policy makers, policy implementers, policy targets, policy evaluators, and expert speakers. Data analysis uses data condensation, data presentation, and conclusion drawing techniques. The results of the study show that from the aspect of context evaluation, GNRM policies have identified the needs of the community in building tolerance. From the aspect of input evaluation, there is cross-sectoral stakeholder involvement but there are still budget and resource limitations. From the aspect of process evaluation, the implementation of the program is running but has not been optimal in reaching all levels of society. From the aspect of product evaluation, there is a positive but not significant impact on increasing the index of religious harmony. Supporting factors include government commitment and stakeholder support, while inhibiting factors include budget limitations, coordination between agencies that are not optimal, and strong narratives of intolerance on social media.